2006
DOI: 10.1038/sj.onc.1209955
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of IGF-IR disrupts mammary ductal morphogenesis and induces tumor formation

Abstract: Overexpression and hyperactivation of the type I insulinlike growth factor receptor (IGF-IR) has been observed in human breast tumor biopsies. In addition, in vitro studies indicate that overexpression of IGF-IR is sufficient to transform cells such as mouse embryo fibroblasts and this receptor promotes proliferation and survival in breast cancer cell lines. To fully understand the function of the IGF-IR in tumor initiation and progression, transgenic mice containing human IGF-IR under a doxycyclineinducible M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 45 publications
4
138
1
6
Order By: Relevance
“…We have also found that some advanced IGF-IR-induced tumors resemble Wnt pathway initiated tumors and contain areas with considerable stromal elements and cytokeratin 5 and 14 positive cells (Jones et al, 2007). However, we have yet to observe tumors that would be classified histologically as spindle-cell tumors.…”
Section: Igf-ir Independence Is Accompanied By An Emtmentioning
confidence: 81%
See 4 more Smart Citations
“…We have also found that some advanced IGF-IR-induced tumors resemble Wnt pathway initiated tumors and contain areas with considerable stromal elements and cytokeratin 5 and 14 positive cells (Jones et al, 2007). However, we have yet to observe tumors that would be classified histologically as spindle-cell tumors.…”
Section: Igf-ir Independence Is Accompanied By An Emtmentioning
confidence: 81%
“…We have shown earlier that IGF-IR overexpression in MTB-IGFIR mice results in the rapid development of multiple mammary tumors (Jones et al, 2007). In this paper, we describe the consequence of eliminating IGF-IR transgene expression in established mammary tumors.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations